Hubungan Teknik Menyusui Amubida Terhadap Puting Lecet di Puskesmas Kombos Kota Manado - Asti Ananta Korompot; Meinita Wulansari; Lisa Ardiningtyas (Universitas Pahlawan Tuanku Tambusai, 2026)
Exclusive breastfeeding coverage in Manado City remains low. Data from the Manado City Health Office in 2024 show that Kombos Health Center recorded a 42.4% coverage rate, down from 48.1% in the previous year. This study aimed to determine the relationship between the AMUBIDA breastfeeding technique and the occurrence of cracked nipples among breastfeeding mothers at Kombos Health Center, Manado City, in 2025. This research used a quantitative method with a cross-sectional design. The population consisted of 95 breastfeeding mothers, and 49 respondents were selected using purposive sampling. Data were collected using observation sheets on AMUBIDA technique practice and nipple condition, then analyzed using the Chi-square test with a significance level of ɑ = 0.05. The results showed that 71.4% of mothers applied the AMUBIDA technique, and 63.3% did not experience cracked nipples. The Chi-square test revealed a significant relationship between the AMUBIDA technique and cracked nipples (p = 0.000 < 0.05). It can be concluded that the AMUBIDA breastfeeding technique effectively reduces the incidence of cracked nipples. Health workers are encouraged to strengthen education and training on the AMUBIDA technique to support maternal comfort and the success of exclusive breastfeeding.